(untitled) (المجلة العراقية للعلوم الاقتصادية, 2018)
The existence of systems of Islamic banking trend is not new nor heresy to say it is a fact exist in the economic system and Islamic world. Since established the idea of ​​Islamic banks and the mechanics work on the basis of the deal is usurious Therefore, methods of dealing differ in Islamic banks than it is in conventional banks, including not contrary to the ethical aspects . Having become Islamic banks and reality to deal him within the country or outside its borders and has expanded its banking of all kinds, it was necessary to show the role of scholars and hardworking in the development of Condition legitimate each of these transactions, particularly emerging, including the functioning of the bank. Among the references who emerged on the Iraqi arena Mr. diligent(Mohammad Mohammad Sadeq al-Sadr) as the study seeks to identify the approach of Mr. Sadr and his opinions in adapting banking activity and will focus on documentary credits as the achievement of the export and import for development need to open a documentary credit bank is an intermediary which for the purposes of repayment exchange for a commitment And here is no different general conditions and mechanisms of opening credit for all banks, as it sees diligent with the majority of scholars that the opening of credit and are paid commissions whether funding a loan or treat speculation and various forms (agency, remittance, or security) is permissible provided it does not punctuated benefits or taboos.